The Influence of Streptococcus mutans Biofilm Formation in a Polymicrobial Environment (Streptococcus gordonii & Porphyromonas gingivalis) - Kriswandini, Indah Listiana; Sidarningsih, Sidarningsih; Hermanto, Adelheid Chrissanda; Tyas, Pinta Rahayuning; Aljunaid, Mohammed Ahmed (European Journal of Dentistry, 2024)
Objectives Biofilms play a vital role in the occurrence or worsening of an infectious disease. Streptococcus mutans is a bacterium with the ability to form biofilms that plays a key role in the development of infectious diseases such as dental caries. The formation of biofilms in S. mutans is mediated by quorum sensing. Inhibiting quorum sensing can be considered as one of the approaches to prevent caries. This study aims to investigate the ability of Streptococcus gordonii and Porphyromonas gingivalis bacteria to inhibit the formation of S. mutans biofilm.Materials and Methods This research was conducted to analyze bacterial biofilm formation and metabolism. The bacteria used are S. mutans (serotype C), S. gordonii (ATCC 5165), and P. gingivalis (ATCC 33277). Biofilm formation was analyzed using the crystal violet assay. Bacterial metabolism was analyzed using the methylthiazol tetrazolium (MTT) assay.Results The results of the crystal violet assay indicate a decrease in biofilm formation in S. mutans when in the presence of S. gordonii and S. mutans in the presence of P. gingivalis. The results of the MTT assay show no significant change in the bacterial metabolism of S. mutans in the presence of S. gordonii and S. mutans in the presence of P. gingivalis. However, S. mutans with the presence of S. gordonii and P. gingivalis show an increase in biofilm formation and bacterial metabolism.Conclusion S. gordonii and P. gingivalis are each capable of inhibiting the formation of S. mutans biofilm in a polymicrobial environment.
Keywords: Streptococcus mutans; quorum sensing; infectious disease; biofilm; caries